2019
DOI: 10.1096/fj.201802068rr
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins differentially regulate cell‐cell adhesion in MDCK cells

Abstract: Plasticity of epithelial cell‐cell adhesion is vital in epithelial homeostasis and is regulated in multiple processes associated with cell migration, such as embryogenesis and wound healing. In cancer, cell‐cell adhesion is compromised and is associated with increased cell migration and metastasis. Aquaporin (AQP) water channels facilitate water transport across cell membranes and are essential in the regulation of body water homeostasis. Increased expression of several AQPs, especially AQP5, is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Moreover, a positive tendency in the correlation analysis between AQP5 and Rac‐GTP expression was reported in human breast cancer tissue, the latter being a GTPase involved in cell migration . Also, AQP5 overexpression in normal epithelial cells (MDCK cells) stimulated cell detachment and dissemination from migrating cell sheets, which could be counteracted by inhibition of Ras . These findings indicated that AQP5 contributes to cancer cell migration,and it is an important prognostic marker protein for breast cancer …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, a positive tendency in the correlation analysis between AQP5 and Rac‐GTP expression was reported in human breast cancer tissue, the latter being a GTPase involved in cell migration . Also, AQP5 overexpression in normal epithelial cells (MDCK cells) stimulated cell detachment and dissemination from migrating cell sheets, which could be counteracted by inhibition of Ras . These findings indicated that AQP5 contributes to cancer cell migration,and it is an important prognostic marker protein for breast cancer …”
Section: Introductionmentioning
confidence: 82%
“…16 Also, AQP5 overexpression in normal epithelial cells (MDCK cells) stimulated cell detachment and dissemination from migrating cell sheets, which could be counteracted by inhibition of Ras. 17 These findings indicated that AQP5 contributes to cancer cell migration,and it is an important prognostic marker protein for breast cancer. 13,14,18 MicroRNA (miRNA), the small non-coding RNAs of approximately 20-22 nucleotides in length, regulates mRNA stability by interacting with the complementary sequence motif of the 3ʹ-untranslated region (UTR) of the target mRNA.…”
Section: Introductionmentioning
confidence: 87%
“…In addition to the major involvement of AQP5 in saliva secretion, AQP5 and other AQPs might likely be implicated in cell proliferation and migration, neuronal signaling, adhesion and apoptosis occurring during SG embryonic development [ 18 , 26 , 43 , 44 ]. The individual role of AQPs in SG embryonic development requires further studies.…”
Section: Physiological Function Of the Aqps In Sgmentioning
confidence: 99%
“…During development and organogenesis, cell proliferation, migration, invasion, and cell-cell adhesion are frequently occurred. In these processes, AQP1, AQP3, and AQP4 have been suggested to be involved in such cellular processes [20][21][22][23][24]. Therefore, AQP5 may also play an important role in these developmental processes, although it is still unclear.…”
Section: Introductionmentioning
confidence: 99%